Role of TIPS in Improving Survival of Patients with Decompensated Liver Disease - Sundeep J. Punamiya; Deepak N. Amarapurkar (International Journal of Hepatology)
Liver cirrhosis is associated with higher morbidity and reduced survival with appearance of portal hypertension and resultant decompensation. Portal decompression plays a key role in improving survival in these patients. Transjugular intrahepatic portosystemic shunts are known to be efficacious in reducing portal venous pressure and control of complications such as variceal bleeding and ascites. However, they have been associated with significant problems such as poor shunt durability, increased encephalopathy, and unchanged survival when compared with conservative treatment options. The last decade has seen a significant improvement in these complications, with introduction of covered stents, better selection of patients, and clearer understanding of procedural end-points. Use of TIPS early in the period of decompensation also appears promising in further improvement of survival of cirrhotic patients.